Who gets renal bone disease before beginning dialysis?. Issue 6464 (26th January 1985) - Cundy, T; Hand, D J; Oliver, D O; Woods, C G; Wright, F W; Kanis, J A
Abstract : To identify patients at risk from renal bone disease we compared the demographic characteristics of 243 patients with end stage renal failure grouped according to the presence (97 (40%] or absence of severe renal bone disease as judged by histological criteria. Youth, female sex, tubulointerstitial types of nephropathy, and a long duration of uraemia were all identified as significant independent risk factors for the development of bone disease. The relative risks from being female and having tubulointerstitial renal disease were separately identifiable when the estimated observation of renal failure was short (less than four years). The identification of patients at high risk from bone disease may clarify the pathogenesis and treatment strategies of renal osteodystrophy.